Bioassay-guided Isolation of Ursolic Acid as the Major Cytotoxic Compound Present in the Methanolic Extract of the Leaves of Arbutus pavarii Pamp. - Groshi, Afaf Al; Nahar, Lutfun; MD Ismail, Fyaz; Evans, Andrew R; Sarker, Satyajit D (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Arbutus pavarii Pamp. (Fam. Ericaceae), an endemic Libyan medicinal plant, is commonly known as “Shmeri”, “Shmar” or “Libyan Strawberry”, and almost exclusively found in the Al-Jabel Al-Akhdar mountainous region in Libya. This plant is a forage species for honeybees and thus, is important for honey production. A. pavarii has long been used in Libyan traditional medicine to treat both gastritis and kidney diseases. Previous limited phytochemical studies on this plant furnished the presence of simple phenolics like arbutin and gallic acid, and polyphenolics including flavonoids and tannins, for example, apigenin, epicatechin, hesperidin, kaempferol, naringin, quercetin and rutin, as well as some triterpenes and sterols. This paper describes, for the very first time, a cytotoxicity assay-guided isolation of the major active compound from the methanol extract of the leaves of A. pavarii, and its identification as ursolic acid (1) by comprehensive spectroscopic analyses. Dhaka Univ. J. Pharm. Sci. 20(3): 267-274, 2022 (June) Centennial Special Issue